Estimation of bed shear stress and settling velocity with inertial dissipation method of suspended sediment concentration in cohesive sediment environments - Chang, Jongwi; Lee, Guan-hong; Ajama, Ojudoo Darius; Li, Wenjian (Frontiers in Marine Science, 2024)
In steady uniform boundary layers, the dynamics of sediment resuspension and transport are controlled by near-bed turbulence, often quantified by bed shear stress, τb. Over the past few decades, various methods have been developed to infer bed shear stress using noninvasive, high-resolution flow observations from acoustic instruments. However, there is room for improvement in these methods. This study adopts an inertial dissipation method for sediment (IDM_Sed) to improve the accuracy of shear stress estimation from suspended sediment concentrations (SSC) and to evaluate IDM_Sed performance in cohesive sediment environments by incorporating more accurate, time- and elevation-varying settling velocities. Comprehensive observations were conducted on the Songdo tidal flats over more than one month in 2023, using both acoustic and optical instruments. Our results suggest that the improved IDM_Sed enhances the accuracy of computed shear stress. In cohesive environments, this method captures trends in shear stress induced by current velocity and incorporates influences from sediment concentration. Moreover, the enhancement of shear stress calculation in IDM_Sed, incorporating SSC and in-situ observed shear velocities, proposes a novel method to compute time-varying settling velocities from shear stress.